H2 Oxidation Electrocatalysis Enabled by Metal‐to‐Metal Hydrogen Atom Transfer: A Homolytic Approach to a Heterolytic Reaction. Issue 41 (19th September 2018) - Chambers, Geoffrey M.; Wiedner, Eric S.; Bullock, R. Morris
Abstract: Oxidation of H2 in a fuel cell converts the chemical energy of the H−H bond into electricity. Electrocatalytic oxidation of H2 by molecular catalysts typically requires one metal to perform multiple chemical steps: bind H2, heterolytically cleave H2, and then undergo two oxidation and two deprotonation steps. The electrocatalytic oxidation of H2 by a cooperative system using Cp*Cr(CO)3 H and [Fe(diphosphine)(CO)3 ] + has now been invetigated. A key step of the proposed mechanism is a rarely observed metal‐to‐metal hydrogen atom transfer from the Cr−H complex to the Fe, forming an Fe−H complex that is deprotonated and then oxidized electrochemically. This "division of chemical labor" features Cr interacting with H2 to cleave the H−H bond, while Fe interfaces with the electrode. Neither metal is required to heterolytically cleave H2, so this system provides a very unusual example of a homolytic reaction being a key step in a molecular electrocatalytic process. Abstract : A cooperative catalysis system using Fe and Cr provides a "division of labor" that enables the electrocatalytic oxidation of H2, even though neither metal is capable of heterolytic cleavage of H2 .